Planning and working with an environmental campaign - Porseryd, Sara (2011)
This thesis deals with the planning and the work of an environmental campaign, and it is based on interviews with people involved with the campaign. I have studied the Miljövänliga veckan (MVV) which means the environment-friendly week. It is held by the Swedish Society for Nature Conservation (SSNC), the biggest environmental organisation in the country. The campaign is about making people more aware of an environmental problem and about changing the consumption behaviour to a more environment-friendly one. I have found three features that according to me seem important in the work and planning of MVV and these are; planning schedule, message and volunteers. The SSNC have a two year planning schedule for each campaign and the message of the campaign is well discussed and very central; there seem to be a lot of thought behind deciding what they want people to do and think and how to make it possible. To be able to go through with the campaign the volunteers are very important. I have made a comparison between the SSNC´s work and two communication strategies; the classical communication model and the Community-based Social Marketing model (CBSM). Both similarities and differences have been found with the two strategies, however the SSNC´s own model has most similarities with the classical communication model.